Parametrização de sistema de irrigação automatizado na cultura do mirtilo orgânico - Feil, Ademar Cézar (2024)
Automated irrigation systems application has been increasing in farming, ergo, it has allowed a better rational management of natural and human resources on several farms. Thus, studies concerning farms, soil and hydrological behavior are essential for determining the parameters of automated systems. Therefore, this study was carried out from January, 01st, 2022 to April, 30th, 2022. Data were collected from the local meteorological station, as well as from Time Domain Reflectometry (TDR) equipment in order to obtain the dielectric constant, to prepare water balance, to record their correlations to analyze the area and make the required adjustments to the irrigation system parameterization. As results, water behavior of soil, effects of rainfall and water depths on water accumulation behavior in soil were obtained. In conclusion, it was recorded that soil volumetric moisture is correlated with water available in soil, and that irrigation system parameterization should be adjusted to provide greater volume in water depth applications.